ARCLib - Lhotak, Martin (Qualitative and Quantitative Methods in Libraries, 2020)
Article informs about the Czech ARCLib project. One of the main goals of the project is the development of an open-source solution for a bit-level and logical preservation of digital documents, respecting the national and international standards as well as the needs of all types of libraries in the Czech Republic. The mission of the ARCLib project lies, among others, in creating a solution that will allow institutions to implement all of the OAIS functional modules and entities, considering institutions’ information model. The architecture is planned as open and modular and the final product will be able to ingest, validate and store data from a majority of software products used for creating, disseminating and archiving libraries’ digital and digitised data in the Czech Republic. The solution is connected to Fedora commons repository and Archivematica, as far as it counts with creation of submission information packages (SIP) using these software solutions.